Time regimes in debt collection and mediation. (November 2019) - Storms, Elias; Verschraegen, Gert
Debt and time are inherently linked. In its essence, a debt is a quantified promise to pay at some point in the future. This article explores the temporal dimension of debt that manifests itself during the process of debt collection, the phase at which indebtedness becomes most tangible. Based on in-depth interviews and ethnographic fieldwork in the world of debt collection in Flanders, Belgium, we analyse how different temporal techniques used by 'street-level' debt collectors incite debtors to pay. Both in collection out of court by collection agencies as well as in judicial enforcement of the obligation to pay, debt collection imposes a strict schedule of repayment on the defaulting debtor. In this 'time regime' imposed upon debtors, payments are closely tracked, so that any deviation can be met by swift reminders and pecuniary punishment. The time regimes of debt collection can conflict with the temporal structures present in the everyday economic lives of the debtors. Incongruences appear due to frictions between the rhythm of repayment on the one hand, and temporal irregularities of the economic lives of debtors on the other. To further explore this time dimension, we also look at how debtors respond and adapt to the new temporal impositions, and how debt mediators deploy temporal strategies when assisting the over-indebted. By negotiating payment plans with creditors, debt mediators mitigate the harsher aspects of the time regime enacted through collection agencies and judicial officers.